PENERAPAN MODEL PROBLEM SOLVING MELALUI PENDEKATAN KONTEKSTUAL PADA MATERI HIDROLISIS GARAM DALAM MENINGKATKAN MOTIVASI BELAJAR DAN HASIL BELAJAR SISWA - Herman Herman; Parham Saadi (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2017)
Abstract. This study aimed to improve the teacher’ performance through self reflection is accompanied by increased motivation and students’ learning outcomes. This study uses the design of classroom action research (CAR) thru two cycles. Each cycle consists of planning, action, observation and evaluation, as well as analysis and reflection. The student samples were class XI IPA 4 SMAN 4 Banjarmasin with 28 students. Data collection technique used observation, recording, cognitive test and learning motivation questionnaire. Data analysis technique used descriptive quantitative and qualitative. The findings showed that there is improvement and enhancement of teacher performance through self reflection from 64.1% in the first cycle to 77.1% in the second cycle, increasing the average score of students' motivation from 100 (enough) at the first meeting of the first cycle to 116.2 (good) in the second cycle, increasing students’ cognitive achievement of 35.71% (fail) the first cycle to 89.29% in the second cycle (good).Keywords: Problem solving models, contextual approach, study motivation, student learning outcomes